« Discipliner les villes coloniales » : la police et l’ordre urbain au Dahomey pendant l’entre-deux-guerres - Bénédicte Brunet-La Ruche (Criminocorpus)
This article is aimed to apprehend the transition from a police of conquest to a police of public urban law after 1920 in Dahomey (now Bénin), a French colony from West Africa. From the control of public hygiene to the repression of vagrancy, this article apprehends the context of this mutation, the fears of authorities related to mobility in colonial cities. The practice of policing sheds light on the meaning of discipline in the colonial environment and the limits of the framing of bodies, more than that of minds.